2021
DOI: 10.3390/molecules26133885
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Suppresses ApoB Secretion and Enhances ApoA-1 Secretion from Human Hepatoma Cells, HepG2

Abstract: The effect of ellagic acid (EA), a naturally occurring polyphenolic compound, on the secretion of apolipoproteins from human hepatocytes, HepG2, was investigated. The levels of apoB and apoA-1 secreted in the cell culture medium were determined by sandwich ELISA. EA did not affect cell viability at the tested concentrations (up to 50 µM). EA suppressed the secretion of apoB and enhanced that of apoA-1 from HepG2 cells. However, cellular apoB levels were increased, suggesting that EA inhibited the trafficking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Moreover, EA treatment could not further increase the CCl 4 -induced cell apoptosis, clearly illustrating that EA enhanced the death of activated HSCs via the ferroptotic pathway rather than the apoptosis pathway. Interestingly, EA-induced HSC ferroptosis has a selective effect; EA neither inhibited growth nor induced ferroptotic events in both primary hepatocytes and human HepG2 cells in normal condition or under injury condition, which is consistent with previous findings that no growth inhibition was observed when hepatocytes and HepG2 cells were treated with 50 μM EA [ 43 , 44 ], suggesting that EA has a selective effect on ferroptosis induction.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, EA treatment could not further increase the CCl 4 -induced cell apoptosis, clearly illustrating that EA enhanced the death of activated HSCs via the ferroptotic pathway rather than the apoptosis pathway. Interestingly, EA-induced HSC ferroptosis has a selective effect; EA neither inhibited growth nor induced ferroptotic events in both primary hepatocytes and human HepG2 cells in normal condition or under injury condition, which is consistent with previous findings that no growth inhibition was observed when hepatocytes and HepG2 cells were treated with 50 μM EA [ 43 , 44 ], suggesting that EA has a selective effect on ferroptosis induction.…”
Section: Discussionsupporting
confidence: 91%
“…Based on T-distributed stochastic neighbor embedding (t-SNE) analysis and differentially expressed gene analysis, we annotated three nonimmune populations and seven immune cell populations. Nonimmune cell types primarily consisted of three hepatocyte subclusters: Hepatocyte (Hep) 1 expressing aqp12 ( 27 ) and itih2 ( 28 ), Hep 2 expressing ahsg1 ( 29 ), apoa1a ( 30 ) and apoa4b . 1 ( 31 ), and Hep3 expressing msmo1 ( 23 ) and hmgcs1 ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mentioned trials showed reductions on total cholesterol and LDL-c. It has been reported the effect of EA upregulating the expression of the LDL-c receptor increasing the LDL-c uptake [ 16 ], and its effect increasing the secretion of the apolipoprotein apoA-1 (major apolipoprotein HDL-c), inhibition of apolipoprotein B (component of LDL-c and VLDL) [ 15 ], and gen-level suppressor action of EA on the microsomal triacylglycerol transfer protein [ 16 ] that mobilizes triglycerides to ApoB. Despite these reported effects, in our study, total cholesterol and LDL-c showed no significant reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar outcomes from an in vitro study were reported by Wang et al [ 14 ], who found that EA inhibited adipogenesis through the suppression of adipocytes differentiation, interrupting the cell cycle [ 14 ]. It has been observed that the consumption of EA improves plasma lipid levels through various mechanisms [ 8 ], like increasing the secretion of apolipoprotein apoA-1, the main apolipoprotein of the high-density lipoprotein cholesterol (HDL-c); and by inhibiting apolipoprotein B, a component of low-density lipoprotein cholesterol (LDL-c) and very low-density lipoprotein (VLDL) [ 15 ]. EA also upregulates the expression of the LDL-c receptor, via the ERK signaling pathway, increasing the LDL-c uptake [ 16 ].…”
Section: Introductionmentioning
confidence: 99%